Application of AHP to support the Marketing Management Promotion Strategy of Universities in Aceh - Yuli Asbar; Sapna Biby; Anggar Pratama; Janner Simarmata; Abror Abror (Institute of Computer Science (IOCS), 2021)
Marketing management promotion strategy is important by private universities, this hall because the high competition with public universities is very high and the number of study programs at public universities in Aceh so that competition to increase prospective students is very tight, especially in the selection of study programs in accordance with student interests. The importance of conducting marketing management promotion strategies in convincing prospective new students to choose a privately schooled program according to the student's interests. Furthermore, the need for a system in providing major recommendations in accordance with interest is one of the strategies to attract students to enroll vocationally. With this recommendation system provides recommendations for students in choosing a major must be on target, effective and efficient. so that students can choose major recommendations with a more effective duration of time, not wasted time and students can choose a study program that suits their grades and abilities. Therefore, it is important that the application model of application of decision support systems using the analitycal hierarchy process for students and this program strongly supports the university in looking at prospective students based on interests and talents that are in accordance with each student's abilities. The keriteria used in the ahp method of student subjects is processed in the ahp model and incorporated into the program for the suitability of majors and study programs. This research flow includes weighting menu to see the level of interest of criteria, menu set weight criteria in accordance with the initial input of criteria, menu set weights majors, menu list of majors to see the majors covered, design values and list of student names that include informatics, accounting and management. Kriteri value 98, 90, 75, 80 and 84, then for K-1 and alternative 1 namely, 0.2940, Alt 0.0702, Alt-3 0.003, alt 4 with a value of 0.4894 and the last stage is 0.01124 with the highest score Alt-1 0.1810, Alt2, 01586, 0, 1047, Alt4 0.4002 and Alt 5 0.1518. In addition, you see majors who are the same age as the campus.